2018
DOI: 10.3390/ijms19103248
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Detection of Extracellular Matrix Metalloproteinase Inducer EMMPRIN, a New Therapeutic Target against Atherosclerosis, Inhibited by Endothelial Nitric Oxide

Abstract: Lack of endothelial nitric oxide causes endothelial dysfunction and circulating monocyte infiltration, contributing to systemic atheroma plaque formation in arterial territories. Among the different inflammatory products, macrophage-derived foam cells and smooth muscle cells synthesize matrix metalloproteinases (MMPs), playing a pivotal role in early plaque formation and enlargement. We found increased levels of MMP-9 and MMP-13 in human endarterectomies with advanced atherosclerosis, together with significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“… Major et al (2002) have demonstrated that CD147 is localized to lesion areas of the human atheromas, where the areas of strong CD147 protein expression coincide with macrophage areas and not to smooth muscle cell areas. In contrast, Ramirez-Carracedo and colleagues ( Ramirez-Carracedo et al, 2018 ) have reported CD147 expression in foam cells, smooth muscle cells, and endothelial cells of vascularized plaques. However, CD147 expression in both studies is only determined by immunohistochemistry, which is lack of specific markers for indicating cell types.…”
Section: Discussionmentioning
confidence: 88%
“… Major et al (2002) have demonstrated that CD147 is localized to lesion areas of the human atheromas, where the areas of strong CD147 protein expression coincide with macrophage areas and not to smooth muscle cell areas. In contrast, Ramirez-Carracedo and colleagues ( Ramirez-Carracedo et al, 2018 ) have reported CD147 expression in foam cells, smooth muscle cells, and endothelial cells of vascularized plaques. However, CD147 expression in both studies is only determined by immunohistochemistry, which is lack of specific markers for indicating cell types.…”
Section: Discussionmentioning
confidence: 88%
“…In this synthesis process, nicotinamide-adenine dinucleotide phosphate (NADPH), tetrahydrobiopterin, Ca +2 / calmodolin, and flavin adenine dinucleotide act as cofactors (Hong et al, 2019). The most important roles of NO is as an endodermal vasodilator that is critical for cardiovascular protection (Ramirez-Carracedo et al, 2018). NO also inhibits platelet aggregation and adhesion, which contributes to the downregulation of chemotactic protein MCP-1 and surface adhesion molecules, such as CD11/CD18, P-selectin, intercellular cell adhesion molecule-1, and vascular cell adhesion molecule-1 (Saini et al, 2012).…”
Section: Glutamine Inhibits Nitrification Stress Caused By Excessive mentioning
confidence: 99%
“…In vivo MRI sequences showed signal enhancement in the carotid wall after NAP9-injection as compared to the control NP. Carotid sections further revealed a strong colocalization of EMMRPIN and NAP9 in atherosclerotic plaques, confirming the potential of NAP9 for molecular imaging targeting inflammation promoting atherosclerotic plaque progression [30].…”
Section: Inflammationmentioning
confidence: 59%
“…Mainly two considerations mark the difference between scientific curiosity and clinical need with regard to these technologies. [34] (THI0567-lipid NP) liposomal NP bearing gadolinium, selective integrin α4β1 antagonist THI0567 and rhodamine [28] (NAP9-lipid NP) paramagnetic micellar NP conjugated with gadolinium, rhodamine and EMMPRIN-specific binding peptide NAP9 [30] (A5-mNP) micellar NP bearing Cy5.5 and rhodamine, gadolinium and polymers, covalently coupled to phosphatidylserine ligand annexin A5 [36] ( 64 Cu-CANF-comb) NPR-C-targeting polymeric positron-emitting nanoparticle (TAP-SiO2@AuNP) gold NP coated with silicon dioxide linked to a thrombin-activatable fluorescent peptide [39] (DDNP) NP based on paramagnetic iron oxide and Indian ink linked to cRGD-and GA-EWVDV-ligands targeting glycoprotein IIb/IIIa and P-selectin on activated platelets [40].…”
Section: Conclusion and Theranostic Perspectivesmentioning
confidence: 99%